The relative importance of the language factor in writing the human resource requirement of the tourism industry in Langkawi - Abdullah, Syaharom; Rao, Ravantharanathe (Universiti Utara Malaysia, 1992)
A good command of the English language is regarded as an asset for a personnel in the tourism industry. However, the preference for those with good English language proficiency has also burdened the recruitment of hotel personnel. The present study employing the questionnaire survey method and interview, which involved 42 English speaking guests staying in four top resorts in Langkawi was conducted to investigate (1) the relative importance of the language factor in the choice of holiday accommodation and (2) the suitable level of English language proficiency for the different groups of hotel staff. The results indicated that English language proficiency was not perceived as the most important personal quality that make up 'quality of service' and that different levels of English language proficiency were required of the various groups of hotel staff. The study concluded that a rigid emphasis on English language proficiency would only unduly hinder the recruitment of hotel personnel and indirectly, the effort to make Langkawi a top choice holiday destination.